EXPLORING LEBANESE CULTURAL DIMENSIONS AFFECTING LEVELS OF UNIVERSITY HR PERFORMANCE - G. Macky, Bassam; J. Hejase, Ale; J. Hejase, Hussin (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Maximizing performance is considered an ultimate goal at business and country levels. Consequently human talent, viewed as an essential organizational asset, is sought after to fit organizational needs to build best practices in performance. However, researchers have found that culture plays a vital role and isconsidered the most dominant and life-long affecting variable on human outcomes. Although culture-oriented applications is becoming a management trend in developed countries, very little or no research is focused on cultural backgroundofhuman resources performance in Lebanon. This paper sheds light on the aforementioned issue and analyzes current cultural attitudes as gleaned from a sample of universities HR in Lebanon.The methodology used is quantitative descriptive. The research tool is a closed-end, five-scale Likert-type questionnairedesignedbased on Hofstede and GLOBE cultural constructs, and used for surveying purposes.The questionnaire is answered by universities HR represented by university staff and instructors selected from a number of Lebanese universities. Questionnaire subscales have been validated using reliability test and factor analysis Varimax rotation method. Hypotheses are tested by computing score means and standard deviations.Research findings serve as recommendations to guide managers and officials to set policies that sustain positive attitudes and isolate negative ones with an aim to maximize HR performance.